The Effect of Using Duolingo on Students' Pronunciation and Fluency at SMA Negeri 5 Bungo - Widuri, Widuri; Sari, Senorica Yulia (Journal of English Language Teaching, 2024)
This research is a pre-experimental design that aims to see the effect of using Duolingo on the students’ pronunciation and fluency of SMA Negeri 5 Bungo students. The population for this research consisted of 10th-grade students SMA Negeri 5 Bungo which amounted to 75 students and the sample of this study was the 10th grade Mipa class which amounted to 24 students selected through the lottery method. The instrument used was reading aloud test in the form of dialog. This research lasted for 8 weeks, in which students were asked to do a pretest in the first week, then treatment for 6 weeks and finally posttest. Data were analyzed using IBM SPSS 26 by conducting hypothesis testing using paired t-test. The findings of this research indicated that the sum of the mean scores of the pre-test was 58.50 and the posttest was 77.88. The results of the paired t-test analysis indicate that the significance value (2-tailed) is < 0.05, which means there is a significant change in students' pronunciation and fluency after utilizing the Duolingo application.